An internal ribosome entry site directs translation of the 3'-gene from Pelargonium flower break virus genomic RNA: implications for infectivity. - Olga Fernández-Miragall; Carmen Hernández (PLoS ONE)
Pelargonium flower break virus (PFBV, genus Carmovirus) has a single-stranded positive-sense genomic RNA (gRNA) which contains five ORFs. The two 5'-proximal ORFs encode the replicases, two internal ORFs encode movement proteins, and the 3'-proximal ORF encodes a polypeptide (p37) which plays a dual role as capsid protein and as suppressor of RNA silencing. Like other members of family Tombusviridae, carmoviruses express ORFs that are not 5'-proximal from subgenomic RNAs. However, in one case, corresponding to Hisbiscus chlorotic ringspot virus, it has been reported that the 3'-proximal gene can be translated from the gRNA through an internal ribosome entry site (IRES). Here we show that PFBV also holds an IRES that mediates production of p37 from the gRNA, raising the question of whether this translation strategy may be conserved in the genus. The PFBV IRES was functional both in vitro and in vivo and either in the viral context or when inserted into synthetic bicistronic constructs. Through deletion and mutagenesis studies we have found that the IRES is contained within a 80 nt segment and have identified some structural traits that influence IRES function. Interestingly, mutations that diminish IRES activity strongly reduced the infectivity of the virus while the progress of the infection was favoured by mutations potentiating such activity. These results support the biological significance of the IRES-driven p37 translation and suggest that production of the silencing suppressor from the gRNA might allow the virus to early counteract the defence response of the host, thus facilitating pathogen multiplication and spread.